OPTIMAL BASKET CURRENCY MODEL: CASE IN INDONESIA - Magdalena (NIM 19014044), Camelia
he previous research done by Yoshino et al. (2017) showed that the use of optimal basket currency model could result in a lower level of GDP compared to the use of free-floating exchange rate regime currently implemented by Indonesia. However, there are only two currencies put in the basket currency which is not likely to represent the real situation in Indonesia. Therefore, this research is conducted to identify the new optimal basket currency arrangement for Indonesia if more than two currencies put in the basket. The currencies put in the basket are from the major trading partner of Indonesia, such as China, Singapore, Japan, South Korea, and the United States. The data will be gathered from the World Bank and Bank Indonesia metadata from 1998 to 2015. The weight of the currency will be formulated by combining the exchange rate relationship model and GDP volatility function. The expected value of the optimal weight of each currency will be simulated by using TwoStage Least Square Regression (2SLS) and the last step is testing the GDP volatility by comparing the standard deviation among the exchange rate regimes. In addition, the result of the proposed basket currency can reduce the GDP volatility of Indonesia.